2018
DOI: 10.1039/c8ra02122h
|View full text |Cite
|
Sign up to set email alerts
|

Lithium sulfonate-grafted poly(vinylidenefluoride-hexafluoro propylene) ionomer as binder for lithium-ion batteries

Abstract: Lithium sulfonate-grafted PVDF-HFP was successfully synthesized and used as binder for lithium ion batteries, improving electrochemical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Among all SIPEs, those based on PVDF have not been widely reported due to the difficulty of synthesis. Up to now, most of the SIPEs were synthesized by covalently grafting the lateral ionic chain onto the VDF backbone by irradiation [48] or reaction with amines [49].…”
Section: Introductionmentioning
confidence: 99%
“…Among all SIPEs, those based on PVDF have not been widely reported due to the difficulty of synthesis. Up to now, most of the SIPEs were synthesized by covalently grafting the lateral ionic chain onto the VDF backbone by irradiation [48] or reaction with amines [49].…”
Section: Introductionmentioning
confidence: 99%
“…14 Recently, the lithiated polymers have been developed as effective binders to improve the electrochemical performances of LIBs ether for LiFePO 4 and LiMn 2 O 4 cathode or graphite/Si anode. 15,[16][17][18][19][20][21][22][23] These lithiated polymers can provide extra lithium-ion, which facilitates the ion transport and thus promotes the high rate performances of the cells. In summary, most of these polymers are the lithiated sulfonate polymers, including perfluorosulfonate, poly(etherether-ketone) and poly(vinylidenefluoride hexafluoro propylene).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, most of these polymers are the lithiated sulfonate polymers, including perfluorosulfonate, poly(etherether-ketone) and poly(vinylidenefluoride hexafluoro propylene). [16][17][18][19][20][21] Additionally, Yuan et al reported the lithiated carboxylate polymer binders with different functions, such as, self-healing and crosslinking. 15,[22][23] Although the lithiated polymers can improve the rate performance of LIBs ether cathode or anode, they also exhibit brittle property due to the metal salt on polymer chain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations